2019
DOI: 10.1186/s40942-019-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of image quality on the reliability of OCT angiography measurements in patients with diabetes

Abstract: BackgroundThis study aimed to determine the relationship between image quality and measurement repeatability of optical coherence tomography angiography (OCTA) parameters in patients with non-proliferative diabetic retinopathy.MethodsA total of 100 eyes of 50 patients were included in the study. Three OCTA images were obtained consecutively during one session of imaging in all patients using the RTVue AngioVue OCTA device. We applied the signal strength index (SSI) provided by the RTVue system to define scan q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…Similar to conclusions suggested by prior authors [ 24 , 30 , 33 , 34 ], our results highlight the importance of using high-quality images with a high level of signal strength when interpreting OCTA metrics, including black diabetic populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to conclusions suggested by prior authors [ 24 , 30 , 33 , 34 ], our results highlight the importance of using high-quality images with a high level of signal strength when interpreting OCTA metrics, including black diabetic populations.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Lim et al found that VD, perfusion density (PD), and FAZ area significantly increased with increased signal strength [ 24 ]. In addition, Czakó et al demonstrated that repeatability of OCTA metrics in diabetic populations are significantly affected by reduced signal strength [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is important since two recent studies showed that OCTA image quality can affect reliability of OCTA quantitative measures. 17,18 Our study has some limitations as well. We limited our inter-instrument repeatability to two instruments and intrainstrument analysis to one instrument.…”
Section: Discussionmentioning
confidence: 95%
“…The measurement error is substantially larger in scans with lower image quality as compared to those with better quality. 47 48 …”
Section: Discussionmentioning
confidence: 99%